Analisis Adaptasi Jurnalis Perum LKBN ANTARA Terhadap Style Book LKBN ANTARA 2012 yang Disosialisasikan pada Januari 2013 - Yuri Alfrin Aladdin; Rustono Farady Marta (Universitas Bunda Mulia, 2013)
A Style book for a print mass media or online media is an important thing to be understood by journalists. In general, a style book provides a unity in using terminology or idiom, furthermore it also contains certain regulations in writing for each media. It’s important for mass media corporation to make its journalists understand and implement what it has established in the style book. We can’t imagine if, for example, a print media with many journalists make different idioms for an institution, which will makeits readers confuse. This research will be focused on the level of adaptation of Perum LKBN ANTARA’s Journalists to the ANTARA 2012’s style book which has been socialized on Januari 2013. The research applies a qualitative method based on an interview with Antara’s journalists, including a contributor, some reporters, some editors, a newsroom manager, anombudsman, and a deputy chief editor. We expect the result of this research would be able to discover the level of journalists adaption to the style book’s socializing, as well as to find the effective way in socializing a style book in order to be fully accepted by the journalists of Antara News Agency (Perum LKBN Antara).Keywords: News Writing, Style Book, Perum LKBN Antara, Antara News Agency